Safety and Immunogenicity of Cuban Antipneumococcal Conjugate Vaccine PCV7-TT in Healthy Adults - Nadezhda González (MEDICC Review, 2015)
INTRODUCTION Pneumococcal infections are a major cause of mor bidity and mortality and are associated with considerable eco- nomic burden on health systems. To prevent pneumococcal infec- tions, 7-valent conjugate vaccines have been available for over a decade; more recently, 10- and 13-valent conjugate vaccines have been for mulated, which are more immunogenic than vaccines with capsular polysaccharides only. In Cuba, a new vaccine candidate has been developed, PCV7-TT, a conjugate of tetanus toxoid with antigens of seven of the serotypes of Streptococcus pneumoniae with highest circu lation in Cuba and in the world: 1, 5, 6B, 14, 18C, 19F and 23F. OBJECTIVE Assess the safety of the vaccine candidate PCV7-TT in healthy adults and conduct a preliminary assessment of its immuno- genicity. METHODS A phase I, double-blind clinical trial was performed at the National Toxicology Center in Havana, Cuba. Healthy male volunteers aged 1835 years were randomly assigned to two groups: 20 received the vaccine candidate PCV7-TT and 20 the polyvalent antipneumo- coccal vaccine PNEUMO-23 used as control, each in a single intra- muscular dose. To assess safety, the occurrence of adverse events was monitored for 30 days following inoculation. To explore immuno- genicity, concentrations of serotype-specific antibodies was quantified before and 30 days after inoculation, as well titers of opsonophago- cytic antibodies. (National Clinical Trial Registry RPCEC00000133) RESULTS Local adverse events were pain, redness, induration, increased sensitivity to touch, and warmth in the injection area. Pain was registered in 70% of individuals who received PCV7-TT and in 75% of those vaccinated with PNEUMO-23. Reported systemic adverse events were general malaise, headache and drowsiness. All adverse events appeared in the first 72 hours post inoculation and lasted no lon ger than 3 days. One event was reported that was clas- sified as severe in intensity and serious in consequences, but it was unrelated to vacci nationacute appendicitis in one individual inocu- lated with the control vaccine. Before vaccination, a ll participants but one had antibody con centrations  0.20 μ g/ml against the vaccine strains; after vaccination 100% of individuals were positive and the concentrations of antibodies increased in previously positive volun- teers. Some individuals had opso nophagocytic antibodies against serotypes 1, 14, 19F and 23F before vaccination, with highest concen- trations against serotypes 14 and 19F. After vaccination, the percent of individuals with opsonophagocytic titers  1:8 for all serotypes in the vaccine was >50% in both groups.